Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Interaction of ARA54 with androgen receptor in mediating testosterone-dependent regulation of caput epididymal GPX5 expression in mice - Dong-li Liu; Xin Gao; Yi-ying Wang; Yu-qing Lin; Si-han Yu; Zhao-jin Luan (Theriogenology, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Mitigation of antibiotic resistance risk in aerobic sludge by zero-valent iron: From pathogen reduction to conjugation inhibition and network weakening - Ying Wu; Lin Zhu; Guoping Lin; Xuezhu Han; Jingpeng Li; Jiaming Yi; Dan Huang; Meizhen Wang (Bioresource Technology, 2026)

Temporal sulfur redox reprogramming enables control-oriented intensification of sulfur-based autotrophic denitrification - Kun Zheng; Han-Bing Xiao; Yi-Lu Sun; Zhou-Yang Li; Jing-Zhe Zhang; Han-Lin Wang; Ai-Jie Wang; Xue-Ning Zhang (Water Research, 2026)

Asymmetric introgression and reticulate evolution result from palaeoclimate-driven range dynamics of the Smilax hispida group in North and Central America - Xin-Yi Fan; Han-Yang Lin; Ya-Lu Ru; Yun-Peng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Chalcopyrite as an indicator of uranium mineralization in the Qigequan deposit, western Qaidam Basin: Constraints from mineralogy, geochemistry, and sulfur isotopes - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Wen-Yi Wu; Chen Zhang; Zhe Chi; Zhi-Lin Cheng; Bin Guo; Yi-Fan Gao (Journal of Geochemical Exploration, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

Regulating cation disorder to stabilize oxygen redox in Li-rich DRX cathodes via Fe substitution - Chia-Ching Lin; Péter Udvarhelyi; Hao-Hsiang Chang; Tsung-Yi Chen; Zhenfei Cai; Yu Zhao; Han-Yi Chen; Denis Y.W. Yu (Chemical Engineering Journal, 2026)

Integrative study of acute ammonia exposure on the skin of the Striped catfish (Pangasianodon hypophthalmus) - Wei-Hsuan Hsiao; Shun-Yi Lin; Ying-Hsien Wu; Han-Chen Ho; Tsunglin Liu; Liang-Chun Wang (Aquatic Toxicology, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Integrative transcriptomic and functional analysis reveals fatty acyl elongases involved in sex pheromone biosynthesis in rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyraloidea) - Ling-Yue Chen; Xiao-Yang Lin; Ke-Xin Wang; Xiao Feng; Hong-Ting Tang; Shuang-Lin Dong; Ling-Ling Zheng; Yi-Han Xia (Insect Biochemistry and Molecular Biology, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

A fountain pen strategy for writing flexible electronics with low-temperature chemical reactive silver ink - Jiayang Lin; Yi Zhao; Jie You; Fangzu Yang; Ren Hu; Jian-Jia Su; Yuanfei Wu; Lianhuan Han; Dongping Zhan (Chemical Engineering Journal, 2026)

Characterization of a novel Era-homolog (AtERG1) in Arabidopsis that is essential for chloroplast development - Yi Lin; Shuangyuan Jia; Chenchen Zhang; Shanshan Chen; Han Xiang; Jiaqi Chen; Ying Yang; Jiawei Chen; Ming Li; Jinwen Liu (Journal of Plant Biochemistry and Biotechnology, 2026)

Mobilized-clay-driven toppling: A new mechanism resolving the “energy paradox” of under-dip slope failure in flysch terrains - Thanh-Tùng Nguyễn; Ivo Baroň; Filip Hartvich; Jiří Havlík; Lenka Kociánová; Jan Klimeš; Jan Černý; Martin Šutjak; Václav Dušek; Cheng-Han Lin; Chia-Han Tseng; Yi-Chin Chen; et al. (Landslides, 2026)

THBS2: the key hub linking breast cancer stroma, immunity, and therapeutic response - Xi Wan; Xinchen Zhao; Yao Lin; Shujie Yang; Han Dai; Yi Li; Xiaoshan Wang (Clinical & Experimental Metastasis, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Functional characterization of STING in large yellow croaker (Larimichthys crocea), a pivotal regulator associated with TRIF, TRAF3, IRF3, and IRF7 in modulating antiviral signaling - Yi Lin Li; Jia Xi Zhang; Jun Chun Tang; Ying Li; Xuan Zhu; Jian Zhong Han; Yong Hua Jiang; Yi Lei Wang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Enhanced label-free SERS detection of uremic toxins in clinical spent dialysate - Han Lee; Jiunn-Der Liao; Yi-Shan Guo; Chung-Yu Wang; Kuan-Hung Liu; Szu-Hsueh Lai; Bo-Shen Lin (Analytica Chimica Acta, 2026)

Is BPA only the tip of the iceberg? Occurrence and risk assessment of 32 bisphenol analogues in landfill leachate - Zhi-Zhong Zhang; Lin-Hui Zhang; Hang Li; Fei Chen; Sakhayana Nikolaevna Danilova; Ming-Han Li; Bing-Feng Liu; Yi-Fan Li; Zi-Feng Zhang (Journal of Hazardous Materials, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Market mechanism design and trading decision model incorporating renewable energy alliances for the future electricity capacity market of China - Ying-zhu Han; Xing-ping Zhang; Li Liu; Jia-lin Li; Qin-liang Tan; Yuan-fei Li; Yi Du (Energy Policy, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Curvature and Slope Control on Turbidity Currents and Sedimentation in Submarine Channels: A Numerical Study - Xinhao Wen; Yuechuan Han; Rui Zhu; Enxian Liu; Xiyan Lin; Yuchen Zhang; Yi Zhao; Yuhui Zhang; Jiajun Feng; Dongmei Tian (Journal of Marine Science and Engineering, 2026)
Submarine channels are critical conduits for sediment transport by turbidity currents, yet the quantitative influence of channel geometry on flow dynamics and sediment segregation remains poorly understood. Based on computational fluid dynamics, we constructed six three-dimensional numerical models of submarine channels with varying curvatures (R1–R3) and axial slopes (R4–R6) using ANSYS Fluent 17.2, with model settings informed by seafloor morphology from the South China Sea. The Eulerian–Eulerian multiphase model coupled with the standard k-ε turbulence model was used to simulate density fields, velocity structures, and sediment distributions. Results show that low-curvature channels exhibit symmetric density evolution and uniform sediment distribution, whereas high curvature induces pronounced asymmetry with a steep outer-bank density front and triggers secondary flow reversal. Increasing curvature also enhances flow thickness and radial mass flux. Increasing axial slope markedly elevates downstream velocity (0.09 to 0.16 m/s), reduces flow thickness, and shifts sediment distribution toward the inner bank without inducing secondary flow reversal. This study provides a parametric comparison of curvature versus slope effects on turbidity current dynamics and sedimentation patterns under fixed-bed, rectangular-channel assumptions. The findings offer a qualitative reference for interpreting sedimentary architectures in deep-water systems such as those in the South China Sea and analogous rift basins. Results are hypothesis-generating, pending further validation with field data and morphodynamic modeling.

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Use of AI-mediated image analysis to investigate the influence of environmental factors and recreational scuba diving on fish activity patterns in a marine protected area - Ching-Han Chang; Dong-Lin Li; Li-Shu Chen; Yi-Ta Shao (Regional Studies in Marine Science, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Stand age drives divergent microbial metabolic limitations and ecosystem multifunctionality between rhizosphere and bulk soils in subtropical Cryptomeria japonica plantations - Shanshan Huang; Yi Jian; Jing Li; Dengjie Zhou; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Lixia Wang; et al. (Soil Ecology Letters, 2026)

Neutrophil extracellular traps in post-traumatic urethral microenvironment promote hypertrophic urethral stricture via the TLR9/NF-kB/Smad3/IL-8 axis - Ye-Hui Chen; Zhi-Bin Ke; Bo-Han Lin; Yi-Cheng Xu; Xue-Yi Xue; Qing-Shui Zheng; Xiong-Lin Sun; Yong Wei; Ying-Chun Liang; Ning Xu (Apoptosis, 2026)

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Rapid enrichment of ternary carbon-fixing microbial consortia from anaerobic sludge via pressurized pre-autotrophic strategy for scalable microbial electrosynthesis - Lin-xiao Li; Tian-tian Yang; Yue Yuan; Yi-lian Han; Qian Zhao; Wen-han Wang; Yue Sun; Xiao-xin Cao; Xin-lei Jiang; Tian Li; Xin Wang (Bioresource Technology, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

In-situ construction of novel dual bismuth–rich Bi4O5Br2/Bi7O9I3 S-scheme heterojunction with enhanced photocatalytic activity for degradation of diverse persistent organic pollutants - Jia-Lin Zong; Hui-Long Wang; Hao Huang; Yi-Hui Zhao; Li-Juan Han; Wen-Feng Jiang (Journal of Environmental Chemical Engineering, 2026)

Statistical optimization of biochar production via high-temperature carbonization through Taguchi and principal component analysis approaches - Jamin Jamir Escalante; Wei-Hsin Chen; Chien-Yuan Su; Po-Han Li; Kun-Yi Andrew Lin; Kanit Manatura (Fuel, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

PEALD-derived ultrathin Al2O3 and MgO interphases on freestanding nitrogen-doped carbon nanofibers for robust potassium-ion battery anodes - Chih-Chieh Wang; Yi-Han Lin; Chia-Yu Chang (Chemical Engineering Journal, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Effects of temperature change pattern on the hatching of zooplankton resting eggs and community structure - Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Han Zhu; Yi-Long Xi (Hydrobiologia, 2026)

Optimizing collaborative management decision-making in large watersheds through seasonal dynamic water quality diagnosis - Yi-Lin Zhao; Han-Jun Sun; Jie Ding; Ji-Wei Pang; Nan-Qi Ren; Shan-Shan Yang (Journal of Cleaner Production, 2026)

A novel mainstream application of aerobic granular sludge for nitrite supply to Anammox: insights from granule size and microbial stratification - Zongshuo Han; Xiaoying Zheng; Wenfei Li; Haidong He; Yi Fan; Tao Lin; Wei Chen (Journal of Cleaner Production, 2026)

Ferrocene carboxylic acid doped nickel iron hydroxide with strong built-in electric field for oxygen evolution reaction - Xin-Jie Tian; Ruo-Xin Wang; Yi-Lin Dong; Yue-Ming Li; Si-Jia Guo; Na Xu; Guanqun Han; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Climate warming, rather than nitrogen deposition, reduces plant diversity and increases community homogenization in a desert steppe - Yi Zhu; Guodong Han; Loïc Pellissier; Mai-He Li; Lin Jiang; Jinglei Tang; Cuiping Gao; Haiyan Ren (Agricultural and Forest Meteorology, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Attached microalgae-simulated plants enhanced multiple-pollutant removal in a tidal flow constructed wetland: quantified efficiencies, pathways, and biological mechanisms - Shu-Han Ge; Mei-Zi Yang; Wei-Yi Qian; Lin-Lan Zhuang; Hai-Ming Wu; Zhuo Chen; Xiao-Xiong Wang; Jian Zhang (Water Research, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Metformin drives the antibiotic resistome in activated sludge by reshaping microbial communities and promoting horizontal gene transfer - Jiaming Yi; Zhengtao Li; Xuezhu Han; Jingpeng Li; Haotian Liu; Lin Zhu; Meizhen Wang (Journal of Hazardous Materials, 2026)

A novel aqueous synthesis of anion exchange membranes for fuel cells - Xia Liu; Zhongshan Feng; Cuiwen Deng; Quan Yang; Minhao Wang; Xinjie Zhang; Yi Hu; Yufan Zheng; Juan Zeng; Bencai Lin; Juanjuan Han (Fuel, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Nonlinear dynamics of rotating graphene-reinforced composite blades under 1:2 internal resonance in fluid-submerged environments - Yi-Han Cheng; Gui-Lin She (Ocean Engineering, 2025)

Relating small waterbody denitrification with ecosystem respiration in an intensive anthropogenic region - Xuemei Zhao; Yi Zhu; Xu Yang; Li Zhang; Xuan Huang; Chunwang Li; Kebing Chen; Han Lin; Dongli She; Yongqiu Xia (Journal of Hydrology, 2025)

Acute skin responses to ammonia in striped catfish (Pangasianodon hypophthalmus) unveil a potential damage-buffering mechanism - Wei-Hsuan Hsiao; Shun-Yi Lin; Tsung-Lin Liu; Han-Chen Ho; Liang-Chun Wang (Fish & Shellfish Immunology, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Microbial recalcitrant-C metabolism and community composition shifts support enhanced thermal adaptation of soil microbial respiration - Gang Huang; Yan-gui Su; Si-nuo Lin; Zheng-yi Huang; Jin-yi Yan; Xiao-han Dai (Soil Biology and Biochemistry, 2025)

Feasibility of one-step nanofiltration driven by ultra-low pressure (LPOSNF) for algae-laden brackish water treatment: insights from the relationship between algal physiological state and membrane fouling development - Dachao Lin; Zhongjian Zhuang; Hualong Zhao; Yi Wu; Xiaobin Ma; Zhihong Wang; Han Zhang; Lifan Liu; Xing Du (Chemical Engineering Journal, 2025)

Preparation of antibacterial CO2-based polycarbonate hydrogels with dual cross-linkages for co-loading of antibiotics and hypoglycemic agents and their applications on diabetic wound dressings - Zheng-Ian Lin; Tzu-Hsien Tsai; Guan-Lin Liu; Chih-Yuan Hsu; Siang-Ming Tsai; Yi-Ping Fang; Wing-Cheung Law; Han-Lin Tsai; Jia-Ying Tsai; Hsuan-Ying Chen; Bao-Tsan Ko; Pei-Wen Cheng; et al. (Chemical Engineering Journal, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

The potential of Cupriavidus sp. DF5525 degrading high concentrations of p-dichlorobenzene - Hong-Lin Ma; Ze-Shen Liu; Qun Han; Yi Yang; De-Feng Li (Journal of Hazardous Materials, 2025)

Contrasting effects of different acid rain types on soil nitrogen pools - Xingyu Pan; Yi Jian; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Algal-bacterial granular sludge cultured with different inoculum: The discrepancy of granulation mechanism and greenhouse gas emissions - Xiongcheng Deng; Xiaoying Zheng; Zongshuo Han; Jiaqing Tao; Yunqing Li; Tianxing Hu; Yi Fan; Tao Lin (Journal of Environmental Chemical Engineering, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Characterizing Gray matter atrophy patterns associated with accelerometer-measured sedentary behavior: a population-based study - Minle Tian; Xiaolei Han; Ming Mao; Xiaomeng Li; Yi Dong; Jiahao Ding; Qinghua Zhang; Shi Tang; Xiaojuan Han; Lin Song; Tingting Hou; Lin Cong; et al. (Brain Imaging and Behavior, 2025)
Evidence has linked self-reported sedentary behaviors with dementia and cognitive impairment; however, the underlying mechanisms remain poorly understood. We investigated the associations of accelerometer-measured sedentary behavior patterns with gray matter atrophy patterns in rural-dwelling older adults, while taking into account the manner in which sedentary time is accrued (in short or long bouts). This community-based study involved 911 dementia-free older adults (age ≥ 60 years, 59% women) who participated in both ActiGraph and brain MRI substudies within MIND-China (2018–2020). Sedentary behavior parameters (total sedentary time, mean sedentary bout duration, and sedentary breaks) were recorded with accelerometers. Regional gray matter volumes (GMV) were measured using voxel-based morphometry (VBM) methods. Data were analyzed using the general linear regression models, restricted cubic spline curves, and VBM analysis. There was an inverted U-shaped association between daily sedentary time and GMV in temporal, cingulate, and medial temporal cortex, while longer mean sedentary bout duration was linearly related to decreased GMV in total, frontal, temporal, insula, cingulate, and medial temporal cortex. Greater daily time spent in light or moderate-to-vigorous physical activity (LPA and MVPA) was correlated with larger insula GMV. The VBM analysis suggested that prolonged daily total sedentary time and mean sedentary bout duration were significantly associated with smaller GMV in extensive brain regions, especially in thalamus and insula. In conclusion, gray matter atrophy associated with sedentary behavior in older adults is characterized by reduced GMV in global, frontal, temporal, medial temporal, and cingulate cortex, especially in the insula and thalamus regions.

Toward more accurate quantification: A review of global large river basin management policies - Yi-Lin Zhao; Han-Jun Sun; Jie Ding; Zhen Hong; Ji-Wei Pang; Guene L. Razack; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2025)

Application of spectral induced polarization technique in monitoring zinc removal by activated carbon as a permeable reactive barrier material - Sheng Zhou; Yi-Xin Yang; Jing-Jing Cao; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Contaminant Hydrology, 2025)

Berberine attenuates the expression of NLRP3 and downstream inflammasome effectors in diabetic retinopathy - Na Li; Ji-Lin Chen; Yi-Jian Sun; Jia-Fan Sun; Ting-Hua Wang; Amy Yi Hsan Saik; Alan Han-Kiat Ong (Journal of Natural Medicines, 2025)

Canopy Exchange Process of Heavy Metals in Subtropical Urban Forest in Southern China - Han-Wen Zhang; Zhi-Yun Jiang; Yi-Hua Xiao; Lin Huang; Shui-Xia Li; Zhi-Gao Fu; Si-Yi Zhang; Yu-Jun Ma (Environmental Processes, 2025)

Large-Scale Aerial Gamma Spectroscopy for Exploring Sandstone-type Uranium Deposits: A Case Study of Gexi Area, Inner Mongolia - Zhe Jiang; XiaoZhong Han; Zhongyue Lin; Hang Hu; Qiang Lai; Yi Gu; ZhaoJian Wu; Xin Zhao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Geochemical remediation and spectral induced polarization monitoring of Cu2+ by geographically abundant paleosol and loess - Yi-Xin Yang; Sheng Zhou; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Water Process Engineering, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

Revealing the characteristics and nitrogen metabolism mechanism of Anammox biofilm assisted by nanoscale zero-valent iron - Zongshuo Han; Xiaoying Zheng; Zhilin Zhao; Wenfei Li; Haidong He; Yi Fan; Tao Lin (Journal of Environmental Management, 2025)

Steroidal saponins and homoisoflavonoids from the fibrous roots of ophiopogon japonicus and their anti-pulmonary fibrosis activities - Hang-Yi Pu; Yu Cao; Xi-Lang Jiang; Lin-Han Yang; Ming-Kui Wang; Fei Wang; Lun Wang (Natural Product Research, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Bisphenol S promotes clear cell renal cell carcinoma progression by modulating the WNT5A-dependent EMT pathway - Hua Zhang; Fei Lin; Bo-Han Lin; Xiong-Lin Sun; Qing-Shui Zheng; Rui Gao; Yong Wei; Shao-Hao Chen; Xue-Yi Xue (Toxicology, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Passivation mechanism driven selective leaching for recycling spent LiFePO4 lithium-ion batteries - Yurong Han; Menglong Yan; Yinzhuang Fang; Yifeng Han; Yi Chen; Liangyou Lin; Jingwen Qian; Tao Mei; Xianbao Wang (Journal of Environmental Chemical Engineering, 2025)

Lifespan extension by rapamycin in Brachionus dorcas (Rotifera) is dose and developmental stage dependent - Ting Liu; Han-Bing Dong; Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Yi-Long Xi (Hydrobiologia, 2025)

Contrasting responses of flowering phenology in C 3 and C 4 plants shape grassland community structure under global change - Lu Bai; Guodong Han; Lin Jiang; Thomas W. Crowther; Constantin M. Zohner; Kailiang Yu; Zhuwen Xu; Zhongwu Wang; Qian Wu; Yi Zhu; Jinglei Tang; Haiyan Ren (Ecology, 2025)
Climate change is known to affect plant phenology. Yet, the sensitivity of flowering phenology in dryland regions to climate change, and the potential implications for community composition, remain largely unexplored. Here, we used an 18‐year field experiment to investigate the effects of climate warming and nitrogen addition on flowering phenology of four C 3 plant species and two C 4 plant species, and the cascading effects on the relative abundance of C 3 and C 4 plants in a desert steppe. Across the past 10 years of the experiment (2013–2022), we found that warming had a greater effect on phenological shifts in C 3 than in C 4 plants. Warming significantly advanced the flowering time of C 3 plants by 4.3 ± 0.1 days and of C 4 plants by 2.8 ± 0.1 days, respectively. Warming also reduced the duration of flowering by 1.8 ± 0.1 days for C 3 plants but had no effect on C 4 plants, and decreased the dominance of C 3 plants compared to C 4 plants. Nitrogen addition extended the duration of flowering of C 4 plants by 3.4 ± 0.2 days and increased their relative dominance, while decreasing the dominance of C 3 plants. Structural equation models revealed that these phenological responses were largely driven by soil temperature and soil water availability. Our results demonstrate that the different phenological responses of C 3 and C 4 plants contribute to shifts in dominance between these plant types in temperate dryland ecosystems under global changes.

Characterization and risk-quantification of antibiotic resistome in grain-based and non-grain cropping soils - Jingpeng Li; Lin Zhu; Xiaodi Li; Xuezhu Han; Jiaming Yi; Ying Wu; Meizhen Wang (Environmental Pollution, 2025)

Formaldehyde oxidation reaction enhanced by interface engineering of Cu/Cu2O/Co(OH)2 composite electrocatalyst for bipolar hydrogen production - Zi Qiang Ma; Chang Bao Han; Wen Kang Zhao; De Cai Fang; Yi Lin Zhao; Chang Xin Liu; Xinxin Wang; Ling Sun; Xue Mei Song (Chemical Engineering Journal, 2025)

Correlation between the utilization of sodium-glucose cotransporter-2 (SGLT2) inhibitors and the risk of dementia: a nationwide population-based study in Taiwan - Wu-Lung Chuang; Stella Chin-Shaw Tsai; Yi-Chun Yang; Tsai-Ling Hsieh; Heng-Jun Lin; Yu-Han Huang; Fuu-Jen Tsai; Kuang-Hsi Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

A novel gravity-driven fixed-bed ceramic membrane filtration (GDFBCM) with critical PAC-MnOx-ceramsite filters for simultaneously removing hazardous manganese and ammonia from groundwater - Dachao Lin; Zhitian Peng; Xiaopeng Zhang; Zhihong Wang; Yi Wu; Xiaobin Ma; Han Zhang; Wei Song; Lifan Liu; Jinxu Nie; Xing Du (Journal of Hazardous Materials, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Atypical absorption response to the trans-thylakoid electric field in the acidothermophilic red algae Cyanidioschyzon merolae and Galdieria partita - Guan-Lin Wu; Shin-Ying Tzeng; Benjamin Bailleul; Julien Sellés; You-Yuan Zhang; Han-Yi Fu (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2025)

Groundwater Level Prediction by Wavelet Deep Learning with Smart Pumping Data - Tsai-Ning Weng; Ray-Shyan Wu; Tzu-Han Weng; Yi-Ho Chen; Tsai-Chun Lai; Jui-Yun Hsieh; Chu-Chun Hsu; Yuan-Chien Lin (Water Resources Management, 2025)

Differences in Pathogenetic Mechanism Between Tibetan and Han High-Altitude Polycythemia Based on a Whole Genome-Wide Association Study - Zhuoma Basang; Shixuan Zhang; Xianwei Ke; Zhuoma Duoji; La Yang; Danzeng Qiangba; Yang De; Deji Gesang; Zixin Hu; Yanyun Ma; Meng Hao; Ruidong Fan; et al. (Phenomics, 2025)

Redox condition changes in the Ross Sea, Antarctica, since the last glacial maximum - Yizhuo Wang; Yi Zhang; Xibin Han; Li Lin; Yukai Hong; Rui Han; Yun Liu; Pengyun Ma; Qian Ge; Xiaohu Li (Acta Oceanologica Sinica, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Optimization of the life cycle environmental impact of shell powder and slag concrete using response surface methodology - Yi Han; Bo Yang; Li-Yi Meng; Hyeong-Kyu Cho; Runsheng Lin; Xiao-Yong Wang (Process Safety and Environmental Protection, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

Geotrichum candidum AGRC-GC1 prevented the decay of pulp from Citri Reticulatae Pericarpium production by inhibiting the growth of spoilage microorganisms - Xue-Ying Han; Jing-Yi Hu; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li; Shuang Li; Jun-Jin Deng (Food Bioscience, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Long-term fallowing produces specific fungal taxa associated with soil carbon storage - Fang LI; Lin CHEN; Yue LI; Yanlai HAN; Yi WANG; Peipei LI; Shuiqing ZHANG; Jiabao ZHANG (Pedosphere, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Sustainable utilization of phosphorus-rich sludge in cement composites: Multiscale evaluation and mechanistic analysis - Shengli Ren; Zhirong Xu; Benqin Yang; Xiao-Yong Wang; Yi Han; Run-Sheng Lin; Yongpang Liao (Journal of Environmental Chemical Engineering, 2024)

Corrigendum to “Response of sulfur-metabolizing biofilm to external sulfide in element sulfur-based denitrification packed-bed reactor” [Environ. Res. 231 (2023) 116061] - Hong-Xu Bao; Han-Lin Wang; Shu-Tong Wang; Yi-Lu Sun; Xue-Ning Zhang; Hao-Yi Cheng; Zhi-Min Qian; Ai-Jie Wang (Environmental Research, 2024)

The Complete Mitochondrial Genome of Chilo infuscatellus (Lepidoptera: Pyralidae), and Related Phylogenetic Analysis - Jiequn Yi; Jianbai Liu; Yongkai Mao; Yinjie Cheng; Minjiang Lin; Hanliang Xu; Yuxing An; Jihu Li; Han Wu (Biochemical Genetics, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

Comprehensive evaluation of the nephrotoxicity of carbon quantum dots: Effects of the surface charge - Pei-Luen Jiang; Yan-Yu Hong; Lingyan Yang; Han-Jia Lin; Chih-Ching Huang; Yan-Hua Chen; Chia-Hua Lin; Yi-Chun Chen (Chemosphere, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Experimental investigation of slamming pressure on 3D bow flare - Yihang Shan; Hui Li; Bingbing Han; Zhiyong Sun; Lin Lu; Ruixiang Liu; Yi Liu; Hao Guo (Ocean Engineering, 2024)

Dietary silicate minerals relieving cadmium or lead poisoning in juvenile sea cucumber, Apostichopus japonicus - Yi Chen; Shuchang Cui; Lin Wu; Yuzhe Han; Xiaoran Zhao; Tongjun Ren (Marine Environmental Research, 2024)

Surface S doping induced ladder-regulation of lattice oxygen on the vertical FeCoOOH for water oxidation - Ning Yu; Ren-Ni Luan; Chao-Yue Gu; Yi-Lin Dong; Guanqun Han; Han Hu; Bin Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

High-contrast electrochromic coatings and devices for health assurance, visual comfort and energy-saving in buildings - Chung-Wen Kuo; Han-Yu Chen; Chen-Hao Yeh; Yuan-Chung Lin; Jeng-Kuei Chang; Pei-Ying Lee; Tzi-Yi Wu (Energy and Buildings, 2024)

Reducing defects in hard carbon graphite domain: Employing a fully dynamic bonding with a multi-crosslinked biomass-based binder for enhanced sodium ion storage - Jiaqi Jiao; Han Lu; Conghua Yi; Dongjie Yang; Xuezhi Zeng; Jinxin Lin; Hongqiang Li (Chemical Engineering Journal, 2024)

Exploring the effects of pemetrexed on drug resistance mechanisms in human lung adenocarcinoma and its association with PGRMC1 - Ssu-Yun Wu; En-Chi Liao; Yueh-Feng Wen; Yi-Shiuan Wang; Han Meng; Hsiu-Chuan Chou; Hong-Lin Chan (Chemico-Biological Interactions, 2024)

Comparative Analysis of Improved YOLO v5 Models for Corrosion Detection in Coastal Environments - Qifeng Yu; Yudong Han; Xinjia Gao; Wuguang Lin; Yi Han (Journal of Marine Science and Engineering, 2024)
Coastal areas face severe corrosion issues, posing significant risks and economic losses to equipment, personnel, and the environment. YOLO v5, known for its speed, accuracy, and ease of deployment, has been employed for the rapid detection and identification of marine corrosion. However, corrosion images often feature complex characteristics and high variability in detection targets, presenting significant challenges for YOLO v5 in recognizing and extracting corrosion features. To improve the detection performance of YOLO v5 for corrosion image features, this study investigates two enhanced models: EfficientViT-NWD-YOLO v5 and Gold-NWD-YOLO v5. These models specifically target improvements to the backbone and neck structures of YOLO v5, respectively. The performance of these models for corrosion detection is analyzed in comparison with both YOLO v5 and NWD-YOLO v5. The evaluation metrics including precision, recall, F1-score, Frames Per Second (FPS), pre-processing time, inference time, non-maximum suppression time (NMS), and confusion matrix were used to evaluate the detection performance. The results indicate that the Gold-NWD-YOLO v5 model shows significant improvements in precision, recall, F1-score, and accurate prediction probability. However, it also increases inference time and NMS time, and decreases FPS. This suggests that while the modified neck structure significantly enhances detection performance in corrosion images, it also increases computational overhead. On the other hand, the EfficientViT-NWD-YOLO v5 model shows slight improvements in precision, recall, F1-score, and accurate prediction probability. Notably, it significantly reduces inference and NMS time, and greatly improves FPS. This indicates that modifications to the backbone structure do not notably enhance corrosion detection performance but significantly improve detection speed. From the application perspective, YOLO v5 and NWD-YOLO v5 are suitable for routine corrosion detection applications. Gold-NWD-YOLO v5 is better suited for scenarios requiring high precision in corrosion detection, while EfficientViT-NWD-YOLO v5 is ideal for applications needing a balance between speed and accuracy. The findings can guide decision making for corrosion health monitoring for critical infrastructure in coastal areas.

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Field performance of 15 rain gardens in different cities in Taiwan - Chi-Feng Chen; Yi-Wei Chen; Cheng-Han Lin; Jen-Yang Lin (Science of The Total Environment, 2024)

High entropy catalysts in electrolytic water splitting: A review from properties to applications - Zhi-Jie Zhang; Ning Yu; Yi-Lin Dong; Guanqun Han; Han Hu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Biocontrol potential of Bacillus velezensis QF-2 isolated from rhizosphere soil of Vickifunkia tianschanica - Tong Shen; Lei Zhang; Zhi-Han Ma; Zheng Gong; Hui-Ming Qi; Hong-Ying Yang; Yi-Lin He (Physiological and Molecular Plant Pathology, 2024)

Tracing residual patterns and microbial communities of pharmaceuticals and personal care products from 17 urban landfills leachate in China - Lin-Hui Zhang; Jin-Nong Li; Yi-Hao Li; Xi-Ze Min; De-Yong Kong; Yue Han; Chao Jiang; Hang Xiao; Bin Liang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

Core microbial taxonomies that maintain high organic carbon content in upland soil - Fang Li; Lin Chen; Zhongjun Jia; Jiabao Zhang; Zhanhui Zhao; Yanlai Han; Yi Wang (Science of The Total Environment, 2024)

Selective catalytic oxidation of DMF over Cu-Ce/H-MOR by modulating the surface active sites - Hua-Hui Xu; Yi-Wei Xian; Xi Zhao; Lin-Ya Xu; Cai-Hao Wen; Han Zhao; Cen Tang; Wen-Zhi Jia; Meng-Fei Luo; Jian Chen (Journal of Hazardous Materials, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

A leaf age‐dependent light use efficiency model for remote sensing the gross primary productivity seasonality over pantropical evergreen broadleaved forests - Jie Tian; Xueqin Yang; Wenping Yuan; Shangrong Lin; Liusheng Han; Yi Zheng; Xiaosheng Xia; Liyang Liu; Mei Wang; Wei Zheng; Lei Fan; Kai Yan; et al. (Global Change Biology, 2024)
Tropical and subtropical evergreen broadleaved forests (TEFs) contribute more than one‐third of terrestrial gross primary productivity (GPP). However, the continental‐scale leaf phenology‐photosynthesis nexus over TEFs is still poorly understood to date. This knowledge gap hinders most light use efficiency (LUE) models from accurately simulating the GPP seasonality in TEFs. Leaf age is the crucial plant trait to link the dynamics of leaf phenology with GPP seasonality. Thus, here we incorporated the seasonal leaf area index of different leaf age cohorts into a widely used LUE model (i.e., EC‐LUE) and proposed a novel leaf age‐dependent LUE model (denoted as LA‐LUE model). At the site level, the LA‐LUE model (average R 2 = .59, average root‐mean‐square error [RMSE] = 1.23 gC m −2 day −1 ) performs better than the EC‐LUE model in simulating the GPP seasonality across the nine TEFs sites (average R 2 = .18; average RMSE = 1.87 gC m −2 day −1 ). At the continental scale, the monthly GPP estimates from the LA‐LUE model are consistent with FLUXCOM GPP data ( R 2 = .80; average RMSE = 1.74 gC m −2 day −1 ), and satellite‐based GPP data retrieved from the global Orbiting Carbon Observatory‐2 (OCO‐2) based solar‐induced chlorophyll fluorescence (SIF) product (GOSIF) ( R 2 = .64; average RMSE = 1.90 gC m −2 day −1 ) and the reconstructed TROPOspheric Monitoring Instrument SIF dataset using machine learning algorithms (RTSIF) ( R 2 = .78; average RMSE = 1.88 gC m −2 day −1 ). Typically, the estimated monthly GPP not only successfully represents the unimodal GPP seasonality near the Tropics of Cancer and Capricorn, but also captures well the bimodal GPP seasonality near the Equator. Overall, this study for the first time integrates the leaf age information into the satellite‐based LUE model and provides a feasible implementation for mapping the continental‐scale GPP seasonality over the entire TEFs.

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Soil organic carbon storage, microbial abundance and pore structure characteristics of macroaggregates across a soil-landscape sequence in a subtropical hilly watershed - Zheng Zhao; Xiao Feng; Chun Liu; Yue Han; Guogang Long; Shuotong Chen; Qingmei Lin; Jingwen Gong; Yi Shen; Ziyi Mao; Thammavongsa Sounilan; Xuhui Zhang; et al. (CATENA, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

High-frequency monitoring during rainstorm events reveals nitrogen sources and transport in a rural catchment - Xuan Huang; Yi Zhu; Han Lin; Dongli She; Ping Li; Man Lang; Yongqiu Xia (Journal of Environmental Management, 2024)

Enzymatic impregnation by high hydrostatic pressure for preparing shape-retaining softened broccoli and carrot - Yu-Hsiang Wu; Bo-Chi Huang; Yan-Han Lin; Chung-Yi Wang (Food Bioscience, 2024)

Phosphine oxide balanced charge transfer hybridization in multi-resonance emitters: towards ∼40% external quantum efficiency and preserved color purity - Su Chen; Yidan Wang; Jincheng Lin; Rundong Tian; Shuang Li; Yi Man; Shuo Chen; Jing Zhang; Chunbo Duan; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Quantitative Applications of Weather Satellite Data for Nowcasting: Progress and Challenges - Jun Li; Jing Zheng; Bo Li; Min Min; Yanan Liu; Chian-Yi Liu; Zhenglong Li; W. Paul Menzel; Timothy J. Schmit; John L. Cintineo; Scott Lindstrom; Scott Bachmeier; et al. (Journal of Meteorological Research, 2024)

Environmental and economic analysis of the transformation of paper mill sludge treatment technologies in China - Yanfei Lin; Guoxia Wei; Hanqiao Liu; Kai Li; Yuwen Zhu; Qianlong Han; Yunzhen Yang; Yi Lian (Environmental Science and Pollution Research, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

MazF-rolling circle amplification combined MALDI-TOF MS for site-specific detection of N6-methyladenosine RNA - Guobin Han; Qiuyuan Lin; Jia Yi; Qian Lyu; Qingwei Ma; Liang Qiao (Analytica Chimica Acta, 2024)

Four new compounds from the fruits of Chinese dwarf cherry ( Prunus humilis Bunge) - Sheng Dong; Ying Zhou; Ji-Chao Wang; Yi-Lin Zhuo; Yi-Han Sun; Jun-Gang Wang; Guo-Gang Zhang (Natural Product Research, 2024)

Alternation of social behaviors for zebrafish (Danio rerio) in response to acute cold stress - Sian-Tai Liu; Chun-Yung Chang; Kuang-Yung Lee; Sok-Keng Tong; Han-Liang Huang; Hsi Chen; Jiun-Lin Horng; Ming-Yi Chou (Fish Physiology and Biochemistry, 2024)

Post-stroke Chinese pure alexia: linguistic features and neuropsychological profiles - Shen-yi Kuang; Yi Xu; Yu-yuan Wang; Zi-gao Wang; Qiang Dong; Xiang Han; Shi-Lin Yang (Acta Neurologica Belgica, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Organic nutrient availability and extracellular enzyme activities influence harmful algal bloom proliferation in a coastal aquaculture area - Lin-Jian Ou; Zhou Wang; Guang-Mao Ding; Feng-Xian Han; Jin-Yi Cen; Xin-Feng Dai; Ke-Qiang Li; Song-Hui Lu (Aquaculture, 2024)

Hazard and risk characterization of 56 structurally diverse PFAS using a targeted battery of broad coverage assays using six human cell types - Lucie C. Ford; Hsing-Chieh Lin; Han-Hsuan D. Tsai; Yi-Hui Zhou; Fred A. Wright; Alexander Sedykh; Ruchir R. Shah; Weihsueh A. Chiu; Ivan Rusyn (Toxicology, 2024)

New modifications of PBAT by a small amount of oxalic acid: Fast crystallization and enhanced degradation in all natural environments - Qingyang Luan; Han Hu; Xingyu Ouyang; Xiaoyu Jiang; Chen Lin; Hanxu Zhu; Ting Shi; Yi-Lei Zhao; Jinggang Wang; Jin Zhu (Journal of Hazardous Materials, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Acetylenic spiroketal enol ethers from Artemisia rupestris and their synergistic antibacterial effects on methicillin-resistant Staphylococcus aureus - Chuan-Yun Xiao; Jiang-Er Lan; Xiao Liu; Zhong-Lin Sun; Xiao-Jin Li; Yi-Han Yin; Simon Gibbons; Qing Mu (Natural Product Research, 2024)

Inhibitory mechanism of esculetin on tyrosinase and browning of fresh-cut apple: New perspectives - Lin-Jun Wang; Qiu-Han Bai; Qiu-Xia Pan; Yi-Feng Wu; Ting-Ting Shao; Yi-Wen Guo; Wen-Shuang Wei; Yi-Ting Wen; Wei-Ming Chai (Postharvest Biology and Technology, 2024)

Synthesis and antifungal activity of 2,4-dihydroxy-5-methylphenyl ethanone derivatives against phytopathogenic fungi in vitro - Lin Jia; Cui-Ping Zhang; Yi Zhu; Chun-Yan Zhao; Zeng-Hui Han; Dong-Bao Hu; Wei Shi (Phytochemistry Letters, 2024)

Mathematical modeling of pickling of bamboo shoot strips and their sulfur dioxide removal during cooking - Chien-Lin Chen; Jheng-Han Tsai; Yeun-Chung Lee; Jen-Yi Huang (Journal of Food Engineering, 2024)

Machine learning-based estimation and mitigation of nitric oxide emissions from Chinese vegetable fields - Zhaoqiang Han; Yi Leng; Zhirong Sun; Haiyan Lin; Jinyang Wang; Jianwen Zou (Environmental Pollution, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Emergence of OXA-48-producing hypervirulent Klebsiella pneumoniae strains in Taiwan - Yi-Tsung Lin; Chien Chuang; Sheng-Hua Chou; Chih-Han Juan; Tsuey-Ching Yang; Barry N. Kreiswirth; Liang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Effect of human chorionic gonadotrophin (HCG) and luteinizing hormone releasing hormone A3 (LHRH-A3) on reproduction and development of brood pouch in Hippocampus erectus - Xuange Liu; Gongpei Wang; Jiahui Chen; Sheng Bi; Chenlei Huang; Han Lai; Huadong Yi; Haiyang Li; Qiuxian Chen; Li Lin; Zhilun Zhang; Xuchong Wei; et al. (Aquaculture, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Modulating in vitro digestion of whey protein cold-set emulsion gels via gel properties modification with gallic acid and EGCG - Yanyun Cao; Qingling Wang; Jinou Lin; Yin-Yi Ding; Jianzhong Han (Food Research International, 2024)

Adapting to seasonal temperature variations: A dynamic multi-subunit strategy for sulfur autotrophic denitrification bioreactors - Yi-Lu Sun; Han-Lin Wang; Huu Hao Ngo; Wenshan Guo; Bing-Jie Ni; Xue-Ning Zhang; Wei Wei (Environmental Research, 2024)

Building a predictive model for hypertension related to environmental chemicals using machine learning - Shanshan Liu; Lin Lu; Fei Wang; Bingqing Han; Lei Ou; Xiangyang Gao; Yi Luo; Wenjing Huo; Qiang Zeng (Environmental Science and Pollution Research, 2023)

Effect of hydraulic regime on sulfur-packed bed performance: Denitrification and disproportionation - Yi-Lu Sun; Wei Wei; Huu Hao Ngo; Wen Shan Guo; Xue-Ning Zhang; Bing-Jie Ni; Wei-Qin Zhuang; Han-Lin Wang (Environmental Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Altered functional brain networks in coronary heart disease: independent component analysis and graph theoretical analysis - Simin Lin; Puyeh Wu; Shaoyin Duan; Qianni Du; Shujia Guo; Zhishang Chen; Naiming Wu; Xiaoyan Chen; Ting Xie; Yi Han; Hengyu Zhao (Brain Structure and Function, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Unlocking the potential of elemental sulfur autotrophic denitrification through inorganic nutrient optimization - Yi-Lu Sun; Xue-Ning Zhang; Han-Lin Wang; Chen-Yang Shao; Wei-Qin Zhuang; Hao-Yi Cheng; Ji-Xian Yang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Adsorption of phosphate in water by La/Al bimetallic-organic frameworks-chitosan composite with wide adaptable pH range - Yi Liu; Dengjie Zhong; Yunlan Xu; Haixing Chang; Lin Dong; Zhuofan Han; Jun Li; Nianbing Zhong (Journal of Environmental Chemical Engineering, 2023)

Flash-ignition of carbon black synthesized from acetylene diffusion flames and its application as ignition agents - Chih-Yung Wu; Yi-Chu Chen; Tse-Hao Wang; Po-Han Lin; Yi-Kuan Kuo (Fuel, 2023)

SERS-based rapid susceptibility testing of commonly administered antibiotics on clinically important bacteria species directly from blood culture of bacteremia patients - Yin-Yi Han; Jann-Tay Wang; Wei-Chih Cheng; Ko-Lun Chen; Yi Chi; Lee-Jene Teng; Juen-Kai Wang; Yuh-Lin Wang (World Journal of Microbiology and Biotechnology, 2023)
Bloodstream infections are a growing public health concern due to emerging pathogens and increasing antimicrobial resistance. Rapid antibiotic susceptibility testing (AST) is urgently needed for timely and optimized choice of antibiotics, but current methods require days to obtain results. Here, we present a general AST protocol based on surface-enhanced Raman scattering (SERS-AST) for bacteremia caused by eight clinically relevant Gram-positive and Gram-negative pathogens treated with seven commonly administered antibiotics. Our results show that the SERS-AST protocol achieves a high level of agreement (96% for Gram-positive and 97% for Gram-negative bacteria) with the widely deployed VITEK 2 diagnostic system. The protocol requires only five hours to complete per blood-culture sample, making it a rapid and effective alternative to conventional methods. Our findings provide a solid foundation for the SERS-AST protocol as a promising approach to optimize the choice of antibiotics for specific bacteremia patients. This novel protocol has the potential to improve patient outcomes and reduce the spread of antibiotic resistance.

Profit-seeking enterprise production and business waste treatment efficiency in Taiwan - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2023)

New furofuran and tetrahydrofuran lignans from the flower buds of Magnolia biondii Pamp and their antiallergic effects - Xing Zhang; Xi-Min Wu; Lin-Hang Han; Fei Qian; Liu-Qiang Zhang; Yi-Ming Li (Natural Product Research, 2023)

Isolation and characterization of 32 SNP markers in Spinibarbus hollandi based on restriction site-associated DNA sequencing (RADseq) - Wenwei Huang; Jiangwei Zhou; Huawei Zhan; Yuying Zhang; Suhan Peng; Wenjun Li; Zusheng Yi; Lin Gui; Chong Han; Qiang Li (Conservation Genetics Resources, 2023)

Degradation of indole via a two-component indole oxygenase system from Enterococcus hirae GDIAS-5 - Jun-Jin Deng; Jing-Yi Hu; Xue-ying Han; Yang Li; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li (Journal of Hazardous Materials, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Biodegradation of p-hydroxybenzoic acid in Herbaspirillum aquaticum KLS-1 isolated from tailing soil: Characterization and molecular mechanism - Yi-Xi Li; Wei Lin; Yong-He Han; Yao-Qiang Wang; Tao Wang; Hong Zhang; Yong Zhang; Shan-Shan Wang (Journal of Hazardous Materials, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

Response of sulfur-metabolizing biofilm to external sulfide in element sulfur-based denitrification packed-bed reactor - Hong-Xu Bao; Han-Lin Wang; Shu-Tong Wang; Yi-Lu Sun; Xue-Ning Zhang; Hao-Yi Cheng; Zhi-Min Qian; Ai-Jie Wang (Environmental Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Assessment of various conditions for the simultaneous determination of US EPA and EU priority PAHs in coffee samples and their PAHs consumption risk - Yu-Fang Huang; Po-Lin Liao; Yi-Jun Lin; Shih-Han Huang; Yi-Hsieng Samuel Wu; Chia-Fang Teng; Deng-Jye Yang (Food Research International, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

An accurate and efficient method for simultaneous determination of 16 trichothecenes in maize and wheat by UHPLC-Q-Orbitrap-HRMS combined one-step pretreatment with a novel isotope multipoint calibration strategy - Yu Wu; Jin Ye; Songshan Wang; Xiaomin Han; Li Li; Lin Zhu; Sen Li; Hongmei Liu; Yang Wang; Yi Shao; Songxue Wang (Food Control, 2023)

Investigating the nonlinear and non-stationary relationship between PM2.5 and air pollutants by wavelet signal analysis in central Taiwan - Shan-Non Feng; Yi-Ho Chen; Tzu-Han Weng; Yuan-Chien Lin (Environmental Geochemistry and Health, 2023)

Enhancing performance and sustainability of ultra-high-performance concrete through solid calcium carbonate precipitation - Yi Han; Runsheng Lin; Xiao-Yong Wang; TaeSoo Kim (Environmental Science and Pollution Research, 2023)

Polyaniline/g-C3N4/Bi2O3/Ti photoanode for visible light responsive photocatalytic fuel cell degradation of rhodamine B and electricity generation - Lin Dong; Yunlan Xu; Dengjie Zhong; Haixing Chang; Jun Li; Yi Liu; Zhuofan Han (Chemosphere, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Protective Effect of Ergothioneine Against Stroke in Rodent Models - Wei-Yi Ong; Mei-Han Kao; Wai-Mui Cheung; Damien Meng-Kiat Leow; Irwin Kee-Mun Cheah; Teng-Nan Lin (NeuroMolecular Medicine, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Advances in the understanding of Blattodea evolution: Insights from phylotranscriptomics and spermathecae - Jin-lin Liu; Jia-wei Zhang; Wei Han; Yi-shu Wang; Shu-lin He; Zong-qing Wang (Molecular Phylogenetics and Evolution, 2023)

Synergistic analysis of performance, functional genes, and microbial community assembly in SNDPR process under Zn(II) stress - Tong Wu; Jie Ding; Le Zhong; Yi-Lin Zhao; Han-Jun Sun; Ji-Wei Pang; Lei Zhao; Shun-Wen Bai; Nan-Qi Ren; Shan-Shan Yang (Environmental Research, 2023)

Post-fire seismic performance of concrete-filled steel tubular column to steel beam joints with blind-bolted connections: Experiment and simulation - Lin-Hai Han; Tian-Yi Song; Shuai Li (Engineering Structures, 2023)

Facile Synthesis of Lanthanum-Doped Fe-Based MOF for Phosphate Removal from Water: High Adsorption Capacity, Tuneability, and Reproducibility - Yi Liu; Dengjie Zhong; Yunlan Xu; Haixing Chang; Lin Dong; Zhuofan Han; Jun Li; Nianbing Zhong (Water, Air, & Soil Pollution, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Analysis of natural disasters and energy efficiency in China - Zhong Fang; Yung-ho Chiu; Tai-Yu Lin; Tzu-Han Chang; Yi-Nuo Lin (Environment, Development and Sustainability, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

The changes of chemical molecular components in soil organic matter are associated with fungus Mortierella capitata K. - Fang Li; Lin Chen; Zhan-Hui Zhao; Yue Li; Hai-You Yu; Yi Wang; Jia-Bao Zhang; Yan-Lai Han (Soil and Tillage Research, 2023)

Using HRMS fingerprinting to explore micropollutant contamination in soil and vegetables caused by swine wastewater irrigation - Wen-Ling Chen; Sih-Yi Yu; Shu-Yen Liu; Sheng-Chi Lin; Tsung-Han Lee (Science of The Total Environment, 2023)

Role of auxin in the symbiotic relationship between Piriformospora indica and rice plants - Po-Chun Lin; Ian Lilananda; Ko-Hsuan Shao; Han-Yi Wu; Shu-Jen Wang (Rhizosphere, 2023)

Carnosic acid attenuated cytochrome c release through the mitochondrial structural protein Mic60 by PINK1 in SH-SY5Y cells - Chia-Yuan Lin; Yi-Chen Huang; Chi-Rei Wu; Han-Ting Wu; Ru-Huei Fu; Chia-Wen Tsai (Food and Chemical Toxicology, 2023)

Alteration of the Gut Microbiota in Missed Abortion - Yi Chen; Xianqian Chen; Pingyu Chen; Xiuxia Chen; Lin Pan; Lihong Han; Tang Zhu (Indian Journal of Microbiology, 2023)
There is a symbiotic relationship between gut microbiota and human beings. Imbalance of the gut microbiota will cause pathological damages to humans. Although many risk factors are associated with missed abortion (MA), the pathological mechanism of it is still unclear. Here, we analyzed gut flora of the patients with MA by S16 high-throughput sequencing. The possible pathogenic mechanisms of the MA were explored. Fecal samples from 14 healthy controls and 16 MA patients were collected to do 16S rRNA gene high-throughput sequencing analysis. The abundance of the Bacteroidetes , Proteobacteria , Actinobacteria , Escherichia , Streptococcus_ Salivarius , and Lactobacillus was significantly reduced in the MA group, while, the abundance of the Klebsiella was significantly increased in the MA patients. The Ruminococcaceae and [Eubacterium]_coprostanoligenes_group were found only in the specimens of the MA patients. The Fabrotax function prediction analysis showed that four photosynthesis function bacteria ( cyanobateria , oxygenic_photoautotrophy , photoautotrophy , and phototrophy ) only existed in the MA group. In the analysis of the BugBase microbiome function prediction, the Escherichia of the MA group is significantly reduced compared to that of the healthy controls in the items of that Contains_Mobile_Elements , Facultatively_Anaerobic , Forms_Biofilms , Potentially_Pathogenic.png , Gram_Nagative , and Stress_Tolerant_relabundance . These alterations may affect the stability of the host's immune, neural, metabolic and other systems by interfering with the balance of the gut microbiota or by the metabolites of those bacteria, causing the MA. This study explored the possible pathogenic factors of the gut microbiota of the MA. The results provide evidence to figure out the pathogenesis of the MA.

Evaluation of toxicity of polystyrene microplastics under realistic exposure levels in human vascular endothelial EA.hy926 cells - Yi-Chun Chen; Ku-Fan Chen; Kun-Yi Andrew Lin; Han-Pang Su; Dong-Ni Wu; Chia-Hua Lin (Chemosphere, 2023)

Evaluating the human use efficiency of urban built environment and their coordinated development in a spatially refined manner - Yi Bao; Zhou Huang; Linna Li; Han Wang; Jiayuan Lin; Gang Liu (Resources, Conservation and Recycling, 2023)

Greenhouse gas emission indicators, energy consumption efficiency, and optimal carbon emission allowance allocation of the EU countries in 2030 - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang; Pei-Yu Lin (Gas Science and Engineering, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Urban park use and self-reported physical, mental, and social health during the COVID-19 pandemic: An on-site survey in Beijing, China - Di Lin; Yan Sun; Yue Yang; Yi Han; Chengyang Xu (Urban Forestry & Urban Greening, 2023)

VUV/UV oxidation performance for the elimination of recalcitrant aldehydes in water and its variation along the light-path - Wan-Yue Ouyang; Wen-Long Wang; Yi-Lin Zhang; Han-Ying Cai; Qian-Yuan Wu (Water Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Comparative pulmonary toxicity assessment of tungsten trioxide and tungsten trioxide hydrate nanoparticles - Hsin Her Yu; Yi-Chun Chen; Han-Pang Su; Liliang Chen; Hung-Hsiang Chen; Kun-Yi Andrew Lin; Chia-Hua Lin (Science of The Total Environment, 2023)

Enhancement of lycopene bioaccessibility in tomatoes using excipient emulsions: Effect of dark tea polysaccharides - Chao Wang; Yinxin Fu; Yi Cao; Jialu Huang; Hongyi Lin; Peiyi Shen; David Julian McClements; Lingyu Han; Tiantian Zhao; Xiaoxuan Yan; Qian Li (Food Research International, 2023)

Statistical optimization of hydrogen production from bio-methanol steam reforming over Ni-Cu/Al2O3 catalysts - Yi-Kai Chih; Wei-Hsin Chen; Siming You; Chun-Han Hsu; Hong-Ping Lin; Salman Raza Naqvi; Veeramuthu Ashokkumar (Fuel, 2023)

Insight into the molecular-level details of αs1 casein interactions with IgG: Combining with LC-MS/MS and molecular modelling techniques - Jianhua Zeng; Kai Lin; Xiaoqian Zhang; Junzhe Zou; Lanwei Zhang; Pimin Gong; Jinlong Zhao; Chunhua Han; Yuhai Liu; Huaxi Yi; Tongjie Liu (Food Chemistry, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Clustered regularly interspaced short palindromic repeats (CRISPR) technology and genetic engineering strategies for microalgae towards carbon neutrality: A critical review - Tse-Min Lee; Jia-Yi Lin; Tsung-Han Tsai; Ru-Yin Yang; I-Son Ng (Bioresource Technology, 2023)

A symbiosis between Euploea butterflies and yeasts - Wan-Rou Lin; Yi-Ping Chang; Hui-Lin Wu; I-Cheng Hsu; Pi-Han Wang (Symbiosis, 2023)

Control measure implications of COVID-19 infection in healthcare facilities reconsidered from human physiological and engineering aspects - Ying-Fei Yang; Yi-Jun Lin; Shu-Han You; Tien-Hsuan Lu; Chi-Yun Chen; Wei-Min Wang; Chung-Min Liao (Environmental Science and Pollution Research, 2022)

Two new phenylpropenoid glycosides from the roots of Illicium dunnianum - Yi-lin Wang; Han Li; Ling Song; Yun-hang Gao; Teng-fei Chen (Natural Product Research, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Assessing the effect of probiotics on tilapia lake virus‐infected tilapia: Transmission and immune response - Ying‐Fei Yang; Jidapa Yamkasem; Win Surachetpong; Yi‐Jun Lin; Shu‐Han You; Tien‐Hsuan Lu; Chi‐Yun Chen; Wei‐Min Wang; Chung‐Min Liao (Journal of Fish Diseases, 2022)
Probiotics have been used to alleviate disease transmission in aquaculture. However, there are limited studies on probiotic use in modulating tilapia lake virus (TiLV). We assessed commercially available probiotic supplements used in TiLV‐infected tilapia and performed mortality and cohabitation assays. We developed a mechanistic approach to predict dose–response interactions of probiotic effects on mortality and immune gene response. We used a susceptible–infected–mortality disease model to assess key epidemiological parameters such as transmission rate and basic reproduction number ( R 0 ) based on our viral load dynamic data. We found that the most marked benefits of probiotics are significantly associated with immune system enhancements (~30%) and reductions in disease transmission (~80%) and R 0 (~70%) in tilapia populations, resulting in a higher tolerance of farming densities (~400 fold) in aquaculture. These findings provide early insights as to how probiotic use‐related factors may influence TiLV transmission and the immune responses in TiLV‐infected tilapia. Our study facilitates understanding the mode of action of probiotics in disease containment and predicting better probiotic dosages in diet and supplements to achieve the optimal culturing conditions. Overall, our analysis assures that further study of rationally designed and targeted probiotics, or mechanistic modelling is warranted on the basis of promising early data of this approach.

Cerebellar Oscillations in Familial and Sporadic Essential Tremor - Shi-Bing Wong; Yi-Mei Wang; Chih-Chun Lin; Scott Kun Geng; Nora Vanegas-Arroyave; Seth L. Pullman; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)

Evaluation of PET List Data-Driven Gated Motion Correction Technique Applied in Lung Tumors - Yi-Lun Chen; Bang-Hung Yang; I.-Ling Shih; Ko-Han Lin (Journal of Medical and Biological Engineering, 2022)

The significance of riparian communities in the energy flow of subtropical stream ecosystems - Yi-Chang Liao; An-Cheng Lin; Han-Ni Tsai; Yu-Ting Yen; Chyng-Shyan Tzeng; Man-Miao Yang; Hsing-Juh Lin (Aquatic Sciences, 2022)

One-Way Intestinal Perfusion of PVP/VA–Poloxamer 188–Curcuma longa L. Extract Solid Dispersion in Rats In Vivo and Its Effect on HSC–T6 Cell Proliferation - Jie Gao; Yi Shi; Yunfeng Han; Xi Tang; Ruohong Bi; Lin Pan; Xianrong Lai (AAPS PharmSciTech, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Propagation and Separation of Downslope Gravity Currents over Rigid and Emergent Vegetation Patches in Linearly Stratified Environments - Ying-Tien Lin; Yi-Qi Ye; Dong-Rui Han; Yu-Jia Chiu (Journal of Marine Science and Engineering, 2022)
Large eddy simulation (combined with the mixture model) and laboratory experiment were used to investigate the impact of emergent and rigid vegetation on the dynamics of downslope gravity currents in stratified environments. The reliability of the numerical model was assessed with the corresponding laboratory measurements. The results show that the vegetation cylinders lead to severe lateral non-uniformity of the current front, causing more evident lobe and cleft structures. In stratified environments, the smaller driving force leads to less propagating velocity until the current separates from the slope. The transition point (from acceleration to deceleration phases) of current velocity appears earlier as the vegetation becomes denser. The peak value of the bulk entrainment coefficient Ebuik is inversely proportional to the vegetation density, while the final converged value of Ebuik is proportional to the vegetation density. Vegetation patches make the degree of fluctuation of the instantaneous entrainment coefficient Einst more intense, and even negative values appear locally, indicating that the gravity current is detrained into the ambient fluid. The velocity profiles of gravity current develop multi-peak patterns in stratified environments due to fingering intrusive patterns. Our analysis reveals that as the vegetation density increases, the generated wakes behind vegetation cylinders increase local entrainment and mixing, causing the density of current flow from vegetation to decrease and reach the neutral buoyancy layer of ambient fluids earlier, finally leading to a smaller separation depth.

miRNA–mRNA Integrative Analysis Reveals the Roles of miRNAs in Hypoxia-Altered Embryonic Development- and Sex Determination-Related Genes of Medaka Fish - Keng Po Lai; Nathan Yi Kan Tam; Yuelong Chen; Chi Tim Leung; Xiao Lin; Chau Fong Tsang; Yin Cheung Kwok; William Ka Fai Tse; Shuk Han Cheng; Ting Fung Chan; Richard Yuen Chong Kong (Frontiers in Marine Science, 2022)
Recent studies have shown hypoxia to be an endocrine disruptor that impairs sex differentiation and reproductive function, leading to male-biased F1 populations in fish. However, the molecular mechanisms through which hypoxia alters fish sex differentiation and therefore sex ratios remain poorly understood. In order to understand the potential role of miRNAs in mediating hypoxia-altered sex determination and differentiation in fish, we conducted small RNA sequencing and transcriptome sequencing on marine medaka ( Oryzias melastigma ) embryos that were exposed to hypoxia (2.0 ± 0.2 mg O 2 L – 1) for 40 h (encompassing a critical window of sex determination). We identified dysregulated miRNAs and mRNAs in the hypoxia-exposed embryo, and bioinformatic analysis of the integrative small RNA sequencing and transcriptome sequencing results revealed hypoxia to cause alterations of genes related to embryonic development through miRNA regulation. Importantly, we have identified miRNA-mRNA pairs that were reported to play roles in gonad development (novel miR-145-col9a3 and novel miRNA-94- arid5b), in sex hormone response (novel miRNA-210-ca2, novel miRNA-106-nr2f2, nbr-miR-29c-nr4a1, and ola-miR-92b-akr1d1), and in sex characteristic development (novel miRNA-145-mns1, nle-miR-20-sord, and ipu-miR-219b-abcc8). Our findings highlighted the possible roles of miRNA–mRNA in regulation of embryonic development and sex determination in response to hypoxic stress.

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

The Significant Role of Radiosonde-measured Cloud-base Height in the Estimation of Cloud Radiative Forcing - Hui Xu; Jianping Guo; Jian Li; Lin Liu; Tianmeng Chen; Xiaoran Guo; Yanmin Lyu; Ding Wang; Yi Han; Qi Chen; Yong Zhang (Advances in Atmospheric Sciences, 2021)

Genetic changes and evolutionary analysis of canine circovirus - Lin Wang; Yifan li; Zhiyuan Guo; Ying Yi; Han Zhang; Haikun Shangguan; Chengshi Huang; Junwei Ge (Archives of Virology, 2021)

Evidence-based Customized Ankle-Foot Orthosis with Energy Storage - Chih-Chun Lin; Chien-Hsien Yeh; Yi-Chun Tsai; Li-Chieh Kuo; Hsiu-Yun Hsu; Ping-Han Chuang; Kai Chang; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Clinacanthus nutans Mitigates Neuronal Death and Reduces Ischemic Brain Injury: Role of NF-κB-driven IL-1β Transcription - Mei-Han Kao; Jui-Sheng Wu; Wai-Mui Cheung; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Deron R. Herr; Teng-Nan Lin (NeuroMolecular Medicine, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Correction to: Application of linked and unlinked co‑transformation to generate triple stack, marker‑free, transgenic white clover (Trifolium repens L.) - Rafael Narancio; Yong-Lin Ding; Yi-Han Lin; Sareena Sahab; Stephen Panter; Matthew Hayes; Ulrik John; Heather Anderson; John Mason; German Spangenberg (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Lactobacillus plantarum PS128 Ameliorated Visceral Hypersensitivity in Rats Through the Gut–Brain Axis - Yen-Wenn Liu; Yen-Po Wang; Hsu-Fang Yen; Pei-Yi Liu; Wen-Jian Tzeng; Chia-Fen Tsai; Han-Chieh Lin; Fa-Yauh Lee; One-Jang Jeng; Ching-Liang Lu; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2020)

Application of linked and unlinked co-transformation to generate triple stack, marker-free, transgenic white clover (Trifolium repens L.) - Rafael Narancio; Yong-Lin Ding; Yi-Han Lin; Sareena Sahab; Stephen Panter; Matthew Hayes; Ulrik John; Heather Anderson; John Mason; German Spangenberg (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Halorussus halophilus sp. nov., A Novel Halophilic Archaeon Isolated from a Marine Solar Saltern - Yi Ding; Dong Han; Heng-Lin Cui (Current Microbiology, 2020)

Description of Gemmobacter aestuarii sp. nov., isolated from estuarine surface water and reclassification of Cereibacter changlensis as Gemmobacter changlensis Chen et al. 2013 - Asif Hameed; Mariyam Shahina; Shih-Yao Lin; Wen-Ming Chen; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Archives of Microbiology, 2020)

Description of Azoarcus nasutitermitis sp. nov. and Azoarcus rhizosphaerae sp. nov., two nitrogen-fixing species isolated from termite nest and rhizosphere of Ficus religiosa - Shih-Yao Lin; Asif Hameed; Chia-Fang Tsai; Guan-Hua Huang; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2020)

Acute physiological responses to combined blood flow restriction and low-level laser - Yi-Ching Chen; Yu-Han Su; Yen-Ting Lin; Chien-Chun Huang; Ing-Shiou Hwang (European Journal of Applied Physiology, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

The response of warm-season precipitation extremes in China to global warming: an observational perspective from radiosonde measurements - Jianping Guo; Yan Yan; Dandan Chen; Yanmin Lv; Yi Han; Xiaoran Guo; Lin Liu; Yucong Miao; Tianmeng Chen; Ji Nie; Panmao Zhai (Climate Dynamics, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Circ_ANKIB1 stabilizes the regulation of miR-19b on SOCS3/STAT3 pathway to promote osteosarcoma cell growth and invasion - Yi-xin Du; Lin-xin Guo; Han-song Pan; Yi-min Liang; Xiang Li (Human Cell, 2020)

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Expansion and evolutionary patterns of GDSL-type esterases/lipases in Rosaceae genomes - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Jiangliu Yu; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Characterization of some selected mud volcanoes of southern Taiwan - Arvind Kumar; Tsung-Han Yang; Vivek Walia; Yi-Chun Sung; Hasio-Fen Lee; Shih-Jung Lin; Kuo-Liang Wen (Acta Geophysica, 2018)

Systematic analysis and comparison of the PHD-Finger gene family in Chinese pear (Pyrus bretschneideri) and its role in fruit development - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Dual therapy with clopidogrel and aspirin prevents early neurological deterioration in ischemic stroke patients carrying CYP2C19*2 reduced-function alleles - Jing Lin; Zhao Han; Chun Wang; Xingyang Yi; Zhenxiao Chai; Qiang Zhou; Ruyue Huang (European Journal of Clinical Pharmacology, 2018)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Effect of Cu(II) on the stability of oxyanion-substituted schwertmannite - Junfei Li; Yingying Xie; Guining Lu; Han Ye; Xiaoyun Yi; John R. Reinfelder; Zhang Lin; Zhi Dang (Environmental Science and Pollution Research, 2018)

Monitoring rubber plantation distribution on Hainan Island using Landsat OLI imagery - Pengpeng Han; Jinsong Chen; Yu Han; Lin Yi; Yannan Zhang; Xiaoli Jiang (International Journal of Remote Sensing, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

The Distal Gut Bacterial Community of Some Primates and Carnivora - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Li Han; Yi Jiang; Xue-Shi Huang; Cheng-Lin Jiang (Current Microbiology, 2018)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Regulatory element-based prediction identifies new susceptibility regulatory variants for osteoporosis - Shi Yao; Yan Guo; Shan-Shan Dong; Ruo-Han Hao; Xiao-Feng Chen; Yi-Xiao Chen; Jia-Bin Chen; Qing Tian; Hong-Wen Deng; Tie-Lin Yang (Human Genetics, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Mechanistic and therapeutic perspectives for cardiac arrhythmias: beyond ion channels - Yufei Wu; Jun Li; Liang Xu; Li Lin; Yi-Han Chen (Science China Life Sciences, 2017)

Follistatin-like protein 1 suppressed pro-inflammatory cytokines expression during neuroinflammation induced by lipopolysaccharide - Kai-Yuan Cheng; Yi Liu; Ying-Guang Han; Jing-Kun Li; Jia-Lin Jia; Bin Chen; Zhi-Xiao Yao; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2017)

Enterovirga rhinocerotis gen. nov., sp. nov., isolated from Rhinoceros unicornis faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Hui Lei; Yi Jiang; Li Han; Xue-Shi Huang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2017)

Retraction Note to: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

Blood Cadmium Level Associates with Lower Testosterone and Sex Hormone-Binding Globulin in Chinese men: from SPECT-China Study, 2014 - Chi Chen; Ningjian Wang; Xiaomin Nie; Bing Han; Qin Li; Yi Chen; Hualing Zhai; Chunfang Zhu; Yingchao Chen; Fangzhen Xia; Meng Lu; Dongping Lin; et al. (Biological Trace Element Research, 2016)

New magnetostratigraphic and pedostratigraphic investigations of loess deposits in north‐east China and their implications for regional environmental change during the Mid‐Pleistocene climatic transition - Lin Zeng; Huayu Lu; Shuangwen Yi; Yongxiang Li; Anqi Lv; Wenchao Zhang; Zhiwei Xu; Haifeng Wu; Han Feng; Mengchun Cui (Journal of Quaternary Science, 2016)
Little is known about the long‐term climatic evolution of north‐eastern (NE) China, because well‐preserved terrestrial paleoenvironmental archives are scarce in this vast region. The extensive loess deposits in the Chifeng region are the thickest and most complete loess–paleosol sequence in NE China, and have significant potential for reconstructing the paleoclimate of the region. Here, we present new high‐resolution magnetostratigraphic results from two loess–paleosol sections in the Chifeng region: the Sanbahuo (SBH) and Toudaojingzi (TDJZ) sections. The results demonstrate that both sections record the Brunhes normal polarity chron and the upper portion of the Matuyama reversed polarity chron. Based on these new results, the base of the TDJZ loess sequence is dated at ca. 1.22 Ma, representing the oldest known loess deposits in NE China. The initiation of loess accumulation in NE China was roughly synchronous with the large expansion of the Eurasian loess belt during the late Early Pleistocene (1.2–0.7 Ma), probably reflecting a widespread intensification of aridity in northern mid‐latitudes. We suggest that global cooling during the Mid‐Pleistocene climatic transition led to increased aridity and more favorable conditions for promoting the availability of silt for entrainment, transport and deposition.

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Ceramics manufacturing contributes to ambient silica air pollution and burden of lung disease - Chung-Min Liao; Bo-Chun Wu; Yi-Hsien Cheng; Shu-Han You; Yi-Jun Lin; Nan-Hung Hsieh (Environmental Science and Pollution Research, 2015)

Adenovirus-mediated osteoprotegerin ameliorates cartilage destruction by inhibiting proteoglycan loss and chondrocyte apoptosis in rats with collagen-induced arthritis - Zhi-yun Feng; Zhen-nian He; Bin Zhang; Yi-qiao Li; Jian Guo; Yuan-lin Xu; Ming-yuan Han; Zhong Chen (Cell and Tissue Research, 2015)

RETRACTED ARTICLE: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Lysobacter lycopersici sp. nov., isolated from tomato plant Solanum lycopersicum - Shih-Yao Lin; Asif Hameed; Cheng-Zhe Wen; You-Cheng Liu; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Production of Arachidonic and Eicosapentaenoic Acids by the Marine Oomycete Halophytophthora - Ka-Lai Pang; Han-Jia Lin; Hung-Yun Lin; Yu-Fen Huang; Yi-Min Chen (Marine Biotechnology, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Description of Algoriphagus taiwanensis sp. nov., a xylanolytic bacterium isolated from surface seawater, and emended descriptions of Algoriphagus mannitolivorans, Algoriphagus olei, Algoriphagus aquatilis and Algoriphagus ratkowskyi - Mariyam Shahina; Asif Hameed; Shih-Yao Lin; Wei-An Lai; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Plant ferredoxin-like protein enhances resistance to bacterial soft rot disease through PAMP-triggered immunity in Arabidopsis thaliana - Yu-Han Su; Chuan-Yu Hong; Yi-Hsien Lin (European Journal of Plant Pathology, 2014)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Putative Pathway of Sex Pheromone Biosynthesis and Degradation by Expression Patterns of Genes Identified from Female Pheromone Gland and Adult Antenna of Sesamia inferens (Walker) - Ya-Nan Zhang; Yi-Han Xia; Jia-Yao Zhu; Sheng-Yun Li; Shuang-Lin Dong (Journal of Chemical Ecology, 2014)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Disruption of Bombyx mori nucleopolyhedrovirus ORF71 (Bm71) results in inefficient budded virus production and decreased virulence in host larvae - Min-Juan Zhang; Ruo-Lin Cheng; Yi-Han Lou; Wan-Lu Ye; Tao Zhang; Xiao-Ying Fan; Hai-Wei Fan; Chuan-Xi Zhang (Virus Genes, 2012)

Bombyx mori nucleopolyhedrovirus ORF54, a viral desmoplakin gene, is associated with the infectivity of budded virions - Min-Juan Zhang; Cai-Hong Tian; Xiao-Ying Fan; Yi-Han Lou; Ruo-Lin Cheng; Chuan-Xi Zhang (Archives of Virology, 2012)

Comparing removal of trace organic compounds and assimilable organic carbon (AOC) at advanced and traditional water treatment plants - Jie-Chung Lou; Chung-Yi Lin; Jia-Yun Han; Wei-Biu Tseng; Kai-Lin Hsu; Ting-Wei Chang (Environmental Monitoring and Assessment, 2012)

Molecular characterization of Antarctic actinobacteria and screening for antimicrobial metabolite production - Learn-Han Lee; Yoke-Kqueen Cheah; Shiran Mohd Sidik; Nurul-Syakima Ab Mutalib; Yi-Li Tang; Hai-Peng Lin; Kui Hong (World Journal of Microbiology and Biotechnology, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease - Wu-Fu Chen; Chiranjib Chakraborty; Chun-Sung Sung; Chien-Wei Feng; Yen-Hsuan Jean; Yen-You Lin; Han-Chun Hung; Tzu-Yi Huang; Shi-Ying Huang; Thung-Ming Su; Ping-Jyun Sung; Jyh-Horng Sheu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Effects of C-terminal amino acids truncation on enzyme properties of Aeromonas caviae D1 chitinase - Fu-Pang Lin; Hsu-Han Chuang; Yi-Hsuan Liu; Chia-Yu Hsieh; Pei-Wen Lin; Hsu-Yang Lin (Archives of Microbiology, 2009)

Cloning and expression study of a putative carotene biosynthesis related (cbr) gene from the halotolerant green alga Dunaliella salina - Chen Chen; Lin Han Bai; Dai Rong Qiao; Hui Xu; Gui Ling Dong; Kun Ruan; Fei Huang; Yi Cao (Molecular Biology Reports, 2008)

Cloning and sequence analysis of the gene encoding 19-kD subunit of Complex I from Dunaliella salina - Yi Liu; Dai Rong Qiao; Hong Bo Zheng; Xu Lan Dai; Lin Han Bai; Jing Zeng; Yi Cao (Molecular Biology Reports, 2008)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

Effects of Cycle Time on Properties of Aerobic Granules in Sequencing Batch Airlift Reactors - Fang Wang; Feng-lin Yang; Xing-wen Zhang; Yi-hui Liu; Han-min Zhang; Jun Zhou (World Journal of Microbiology and Biotechnology, 2005)